Perencanaan Strategi Sistem Informasi Dalam Meningkatkan Daya Saing Sekolah Pada SMK Komputer Mandiri Banjarbaru - - STMIK Banjarbaru, Panca Anitasari WH (APMMI - Asosiasi Profesi Multimedia Indonesia)
Abstract – Vocational secondary school is one of the formal education that produces graduates labor ready students for stakeholders in the field of management, technology and communication. Currently SMK Komputer Mandiri felt the need to hold a good improvement of the quality of human resources who are less skilled in utilizing technology in the process of learning, technology, as well as supporting facilities information system used still less updates. In the face of the development of the systems and information technology to improve the quality of graduates and face global competition, then needed a strategic planning for the development of systems, technology and information management from the school itself. Strategic planning of information systems to improve the quality of graduates and face global competition is carried out by a factor of Five and Force Valuechain Porter. The results of the strategic planning information system showing the upcoming information systems strategic planning using the MCFarlan's portfolio.Key words: information system Strategy Planning, Vocational high school, Value chain, Porter Five Force, Mc Farlan Abstrak – Sekolah Menengah Kejuruan merupakan salah satu pendidikan formal yang menghasilkan lulusan tenaga kerja siap didik untuk para stakeholder dibidang manajemen, teknologi dan komunikasi. Saat ini SMK Komputer Mandiri merasa perlu mengadakan perbaikan baik dari kualitas SDM yang kurang terampil dalam memanfaatkan teknologi dalam proses belajarnya, fasilitas penunjang teknologi, maupun sistem informasi yang digunakan masih kurang update. Dalam menghadapi perkembangan sistem dan teknologi informasi untuk meningkatkan kualitas lulusan dan menghadapi persaingan global, maka diperlukan suatu perencanaan strategis untuk pengembangan sistem, teknologi dan manajemen informasi dari sekolah itu sendiri. Perencanaan strategis sistem informasi untuk meningkatkan kualitas lulusan dan menghadapi persaingan global dilakukan dengan Valuechain dan Five Force Faktor Porter. Hasil Perencanaan Strategis Sistem Informasi menampilkan perencanaan strategis sistem informasi mendatang dengan menggunakan portofolio MCFarlan.Kata kunci: Perencanaan Strategi Sistem Informasi, Sekolah Menengah Kejuruan, Value chain, Five Force Porter, Mc Farlan